This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Note that x has to be odd, for if x is even then we would arrive at y 2 ≡ 3 ( m o d 4 ) which is not possible.
Adding 1 on both sides the equation becomes y 2 + 1 = x 3 + 8 = x 3 + 2 3 .
And since x was odd, lets say x = 2 n + 1 . So we have y 2 + 1 = ( 2 n + 1 ) 3 + 2 3 . Using the formula x 3 + y 3 = ( x + y ) ⋅ ( x 2 − x y + y 2 ) we have y 2 + 1 = ( 2 n + 3 ) ⋅ ( 4 n 2 + 4 n + 1 − ( 4 n + 2 ) + 4 ) = ( 2 n + 3 ) ⋅ ( 4 n 2 + 3 )
Now 4 n 2 + 3 is congruent to 3 ( m o d 4 ) so has atleast one prime divisor p which is ≡ 3 ( m o d 4 ) . But this prime divisor p will divide y 2 + 1 which is absurd, since y 2 ≡ − 1 ( m o d p ) is solvable iff p ≡ 1 ( m o d 4 )